Assessment of NDMU BS Computer Science Student Trainee Performance During On-the-Job Training Using Performance Appraisal Reports (2023–2025) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed the performance of Bachelor of Science in Computer Science (BSCS) student trainees from Notre Dame of Marbel University (NDMU) during On-the-Job Training (OJT) across three summer terms (2023–2025) using a multidimensional performance appraisal instrument completed by host supervisors. A descriptive quantitative design was employed with 30 BS Computer Science trainees from NDMU (Summer 2023: n=5; Summer 2024: n=16; Summer 2025: n=9) deployed to nine host organizations in South Cotabato and surrounding regions. The performance appraisal instrument comprised three parts: Part I assessed Personal Skills and Attitude across four dimensions (Work Habits, Work Skills, Social Skills, General Attitude) using a 5-point scale; Part II evaluated Internship Job Performance across six dimensions using categorical ratings (Not Satisfactory, Satisfactory, Very Satisfactory); and Part III measured alignment with three Program Educational Objectives (PEOs) using a 5-point scale. Data were analyzed using descriptive statistics (means, standard deviations, frequencies, percentages). Part I yielded an overall mean of 4.69 (SD=0.53), with General Attitude highest (M=4.83) and Work Skills lowest (M=4.57). In Part II, Teamwork Skills received the highest Very Satisfactory rate (96.7%) while Job Specific Skills received the lowest (66.7%). Part III overall mean was 4.67 (SD=0.47), with PEO3 highest (M=4.77) and PEO2 lowest (M=4.57). A consistent upward performance trend was observed across terms (2023→2024→2025). The NDMU BS Computer Science trainees demonstrated strong overall performance particularly in professional dispositions, teamwork, and continuous learning. Findings support targeted interventions to strengthen technical skill application and ethical competency development.